A new species of the genus Hoplobatrachus Peters, 1863 (Anura, Dicroglossidae) from northwestern Thailand - Thongproh, Prapaiporn; Chunskul, Jidapa; Sringurngam, Yutthana; Waiprom, Likhit; Makchai, Sunchai; Cota, Michael; Duengkae, Prateep; Duangjai, Sutee; Hasan, Mahmudul; Chuaynkern, Chantip; Chuaynkern, Yodchaiy (Agriculture and Natural Resources, 2022)
Importance of the work: Northwestern Thailand lacks any intensive survey of amphibian fauna; thus, this area is suspected to have undiscovered populations of amphibians. Therefore, conducting field surveys in such areas is essential to fill knowledge gaps about species richness in this animal group. Objectives: To describe a new species of frog genus Hoplobatrachus as new to science. Materials & Methods: A new species was described based on specimens collected from Salawin National Park, Mae Sariang District, Mae Hong Son province, northwestern Thailand. The new species was separated from its congeners inferred from molecular (16S and Cytb genes) and morphological information. Results: The new species was distinguished from its congeners based on mitochondrial DNA sequence analyses and morphological comparisons. The species was characterized by the following characters: pointed snout; large size (snout-vent length [SVL] of adult males = 94.8–102.4 mm, SVL of females = 93.2–96.3 mm); presence of mid-dorsal stripe; absence of thin stripe on inner side of tibia; presence of sexual dichromatism; yellow external vocal sac; presence of nuptial pad on base of first finger in adult males; relative length of finger II < IV < I < III, toe I < II < V < III < IV. Main finding: A new frog species was described based on specimens from Thailand.